2005
DOI: 10.1111/j.1467-9280.2005.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Affirmation of Personal Values Buffers Neuroendocrine and Psychological Stress Responses

Abstract: Stress is implicated in the development and progression of a broad array of mental and physical health disorders. Theory and research on the self suggest that self-affirming activities may buffer these adverse effects. This study experimentally investigated whether affirmations of personal values attenuate physiological and psychological stress responses. Eighty-five participants completed either a value-affirmation task or a control task prior to participating in a laboratory stress challenge. Participants wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
307
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(344 citation statements)
references
References 33 publications
31
307
3
3
Order By: Relevance
“…By contrast, individuals with low global self-esteem -who may not have the same range of positive resources available to ameliorate feelings of threatened self-worth -may require an external manipulation in order to boost their self-integrity. Whilst this would seem consistent with the findings reported by Spencer et al (2001), it is notable that Creswell et al (2005) found that individuals with a positive self-concept (which included high levels of global self-esteem) benefited the most from a self-affirmation manipulation aimed at reducing stress, compared to self-affirmed individuals with a negative selfconcept.…”
Section: The Moderating Impact Of Global Self-esteem On Self-affirmatsupporting
confidence: 74%
See 1 more Smart Citation
“…By contrast, individuals with low global self-esteem -who may not have the same range of positive resources available to ameliorate feelings of threatened self-worth -may require an external manipulation in order to boost their self-integrity. Whilst this would seem consistent with the findings reported by Spencer et al (2001), it is notable that Creswell et al (2005) found that individuals with a positive self-concept (which included high levels of global self-esteem) benefited the most from a self-affirmation manipulation aimed at reducing stress, compared to self-affirmed individuals with a negative selfconcept.…”
Section: The Moderating Impact Of Global Self-esteem On Self-affirmatsupporting
confidence: 74%
“…By contrast, comparatively little research has directly tested the potential moderating role of self-esteem on self-affirmation effects (Creswell et al, 2005;Spencer, Fein & Lomore, 2001;van Dijk et al, 2011) It has been suggested (e.g., Pietersma & Dijkstra, 2012;Sherman & Cohen, 2006) that individuals with low self-esteem might benefit more from self-affirmation when faced with threatening information, because they do not have ready access to the same range of positive self-feelings as individuals with high self-esteem. Thus, they may require an explicit self-affirmation manipulation to negate any threat to selfintegrity posed by threatening information.…”
Section: Self-affirmation Theory and Self-esteemmentioning
confidence: 99%
“…Self-affirmation has also been found to reduce negative emotions and relatively increase need satisfaction, flow, and meaning in life , as well as buffer physiological responses to stressful situations (Creswell et al, 2005;Sherman, Bunyan, Creswell, & Jaremka, 2009), and boost academic outcomes (Cohen, Garcia, Apfel, & Master, 2006;Cohen, Garcia, Purdie-Vaughns, Apfel, & Brzustoski, 2009). Taken together, these benefits of one simple positive activity can intervene at multiple points of the risk-factor-to-disorder trajectory.…”
Section: Positive Activities Can Interrupt Ruminationmentioning
confidence: 98%
“…These new directions in behavior therapy challenge us to develop theoretically coherent, practical, and psychometrically sound assessment strategies. Furthermore, although this study focused on values in terms of their clinical relevance, interest in valued living is extending into related disciplines (e.g., Cohen, Garcia, Apfel, & Master, 2006;Cresswell et al, 2005;Crocker, Niiya, & Michowski, 2008), and shared assessment strategies can facilitate communication and progress across these disciplines. Finally, the availability of appropriate instrumentation makes it more likely that the interest in values and related processes will continue to grow, and that progress in this area will accelerate.…”
Section: Discussionmentioning
confidence: 99%